iAssist versus conventional total knee arthroplasty in patients with varus and valgus deformities - Vanniar, Senthur Rajendren; Wang, Li Ming; Yao, Qing Qiang; Pavan Maddali, Taraka Venkata (International Journal of Research in Orthopaedics, 2018)
Background: Accelerometer and gyroscope based iAssist system’s accuracy in restoring the hip knee angle (HKA) in valgus and varus deformity patients is compared to that of conventional system. Methods: In this retrospective study we compared the HKA of 26 patients in iAssist group with that of 26 patients in conventional group. The knee joints were evaluated with full leg length radiographs. Results: The iAssist group patients’ post-operative hip knee angle was much near to our target angle when compared to that of patients in conventional technique group. Conclusions: iAssist brings the high accuracy associated with large console CAS systems with lower costs and helps surgeons in low volume hospitals achieve specific intra operative goals with the familiarity of conventional guides.